Eating With Your Eyes: How Packaging Visual Cues Affect Content Estimation and Self-control in Virtue and Vice Food. Issue 2 (3rd April 2019) - Scarpi, Daniele; Pizzi, Gabriele; Pichierri, Marco
Abstract: This research investigates the effects of visual cues depicted on food packaging on consumers' estimates of the contained amount and consumers' self-control intentions. Results from two experiments show that the number of product units shown on the package drives perceptions and behavioral intentions in food categories where product size tends to be quite standardized, supporting the "see more, expect more" effect reported by previous literature, but adding a "see virtue, expect more" effect triggered by product type. Instead, when product size tends to vary across manufacturers, picture size has a greater effect on consumers' content estimations and self-control intention than the number of product units depicted, suggesting the existence of a "see small, expect more" effect according to which consumers estimate larger content when the package portrays smaller product units. Results stimulate awareness of the effects that can be conveyed by images on packaging, on content estimates and consumer self-control.